ANALYSIS OF THE INFLUENCE OF CORPORATE GOVERNANCE ON BANKRUPTCY RISK REGISTERED COMPANIES ON THE INDONESIAN STOCK EXCHANGE - Robby Krisyadi; Selin Selin (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
Several countries have entered the second phase of the current pandemic and the shock is likely to occur in the wake of firm bankruptcy risks and a significant increase in leverage, depressing investment and job creation for a long time. The objective of this research is to indicate the effect of corporate governance on insolvency risk. The logistic regression method was applied in this study to sample data on company financial statements that had been determined and registered on the Indonesia Stock Exchange (IDX) from 2017 to 2021 and then processed using the SPSS application. The results of the logistic regression test interpret that the variables of audit committee presence, and audit committee meetings are provide a significant and positive relationship to the corporate insolvency risk variable. In addition, the variables of audit committee size, audit committee independence, audit committee expertise and board size are able to provide a significant and negative relationship to the corporate insolvency risk variable. Independence board meeting variable is not significant to corporate insolvency risk variable.